Screening for Acute Malnutrition Using Family Mid-Upper Arm Circumference in Somali Region of Ethiopia - Olusola Oladeji; Paul Mudzongo; Rashid Abdulai; Abdi Fekdid Mursel; Mohamed Badel Ali; Bashir Sheik Mohammed (International Journal of Nutrition Sciences, 2022)
Background: In spite of the decentralization of diagnosis and treatment of severe acute malnutrition from the strictly hospital-based approach for all cases to community-based approach, only about 10%-15% of the estimated 16.5 million children suffering from severe acute malnutrition have access to treatment. The study assessed the use of Family Mid Upper Arm Circumference (Family -MUAC) for screening of acute malnutrition in Somali Region of Ethiopia.Methods: This study used mix of qualitative and quantitative methods of data collection and analysis to describe the process and outcome of a pilot project using mentor mothers to screen for acute malnutrition among children under five using Family MUAC. This was conducted in 5 districts (woredas) of Somali Region of Ethiopia.Results: Between 73 and 91 percent of the mentor mothers across the five project sites were able to correctly use the MUAC tape immediately after the training. Children correctly diagnosed as severe acute malnutrition (SAM) during the first month of the project by the mentor mothers ranged from 70.0 % to 83.8%, but the accuracy of measurement reduced at the end of the 6 months project period to between 59.8% and 66.7% across the 5 project woredas (districts). The SAM referrals by mentor motherscontributed between 10% and 36.2% of all cases of SAM admitted in the project woredas over the 6 months period.Conclusion: This study demonstrated the ability of mentor mothers to use the color coded MUAC tape to detect severe acute malnutrition among children.